Construção de cenário para uma refinaria de petróleo com baixa escala e não integrada: um estudo de caso - Satt Junior, Sérgio (Universidade do Vale do Rio dos Sinos, 2012)
In the current business environment, there are certain events with high uncertainty that make predictability difficult; thus, companies and their managers must be prepared to act in new and different business environments. Changes in the environment of oil refining in Brazil began with the opening of the fuel market in 1997, since Law 9,478/97 enabled other agents, in addition to Petrobras, to participate in activities related to the import and export of oil products. The refining segment in Brazil has experienced cycles with low and high prices because they have not been adjusted at the same speed as the ones of oil products in the international market. From this perspective, non-integrated refineries were analyzed in this study, mainly the Riograndense Oil Refinery, which has shown lower profitability than integrated ones. Therefore, potential competitive advantages that enable the business to support this type of refinery in the long term were identified. The method of building Global Business Network (GBN) scenarios was applied in order to create future scenarios which can suggest alternatives to a small-scale and non-integrated oil refinery. Besides, the contributions that the method of building GBN scenarios brought to the company and its managers were verified. This qualitative and exploratory research used action research to better describe scenario building in the company. Results generated two scenarios (Maverick and Revolution) for the future of the Riograndense Refinery; they showed distinct paths to be followed in the refining segment, taking into consideration the future of the business environment and the characteristics of the company, i. e., a small-scale and non-integrated oil refinery. The study concludes that the method of constructing GBN scenario helps to improve the perception of the company and its managers about the future of the business environment, reducing errors in the process of decision making. In addition, future directions for the company to survive in an environment with strong competition and environmental constraints could be identified. Furthermore, the GBN method proved to be flexible concerning the characteristics of the company since it valued managers’ knowledge and experience and encouraged them to get involved in the process of scenario building.
Keywords: Refinaria de Petróleo Riograndense; Refinaria não integrada; Planejamento estratégico; Construção de cenários; Método global business network; Riograndense Oil Refinery; Non-integrated refinery; Strategic planning; Scenario building; Global business network method; ACCNPQ::Ciências Sociais Aplicadas::Administração